PENGARUH GROWTH OPPORTUNITY, OPERATING CASH FLOW DAN INTENSITAS MODAL TERHADAP KONSERVATISME AKUNTANSI DENGAN LEVERAGE SEBAGAI VARIABEL MODERASI - Andini Septiani; Inge Lengga Sari Munthe; Fatahurrazak Fatahurrazak (CV. Denasya Smart Publisher, 2026)
The purpose of this study is to examine the influence of Growth Opportunity (GO), Operating Cash Flow (OCF), and Capital Intensity (IM) on Accounting Conservatism (KA), with Leverage (LEV) as the moderating variable. The research population comprises energy sector companies listed on the Indonesia Stock Exchange (BEI) for the 2021–2023 period. The number of companies meeting the sample criteria was 93. Data were obtained from audited annual financial reports. After the outlier removal process, the observations used amounted to 110 out of an initial 129 observations. Data analysis was conducted using multiple linear regression and Moderated Regression Analysis (MRA) with SPSS 26. The results show that GO, OCF, and IM have a significant influence on KA. Leverage is proven to moderate the relationship between GO and OCF on KA, but does not moderate the relationship between IM and KA.